Women Managers In Domestic And International Call Centers - Negi, Naveen (International Journal of Psychosocial Rehabilitation, 2019)
Transnational factories in many regions of Asia, the Caribbean, and Latin America have long viewed women as the "ideal" employees because of their low wages and high productivity. A job in a call center can be considered the essence of the stereotypical ’women’s role’ in the workplace. Skills linked with hegemonic femininity, such as being pleasant, making customers feel comfortable, and handling upset customers, are essential for providing good service over the phone. Interestingly, at some of New Delhi’s burgeoning contact centers, gender segregation is not the norm. Call center employers, educators, and employees all agree that their workplaces are completely inclusive of people of all gender identities. However, despite these promises of occupational desegregation, one still encounters signs of gendered processes in global call centres.